First-year college students’ perceptions of their experiences using information and communication technologies in higher education - Kearns, Sara K. (Kansas State University, 2013)
The increasingly integrated presence of Information and Communication Technologies (ICTs) on university campuses in recent decades has prompted calls for a better understanding of how students use ICTs in higher education, including the transition to college. While research indicates that students with higher self-efficacy are more likely to persist in college, current research makes few connections between students’ self-efficacy with ICTs and persistence. Additionally, researchers in the area of student retention call for educators to understand how their students perceive the college’s cultural environment so as to help students fit in at an institution and persist. Exploration of ICTs as part of a student’s social, academic, and cultural experiences at the university offers educators and administrators the possibility of modifying the college’s cultural properties in response to student needs. This qualitative study investigated first-year college students and their use of technologies to address the following research question: How do first-year college students perceive their experiences using Information and Communication Technologies (ICTs) in the higher education environment? Employing interviews and a phenomenological approach, this study explored the experiences of 19 undergraduate students. Six faculty members or instructors were interviewed about their teaching experiences with first-year students and the extent to which ICTs were incorporated in those experiences in order to provide triangulation of data. Through the analysis of interview transcripts and open coding, three themes emerged regarding how students experience ICTs in higher education. Statements from students and faculty suggest that students experienced ICTs in higher education as: a process of academic integration; situations for which they held internal or external loci of control when using them for academic purposes; and tools to use when becoming socially integrated into the university. The findings of this study have the potential to assist university faculty, instructors, and other staff who are designing courses and services for first-year students. First, the study’s findings indicate that instructors need to be as explicit as possible with their expectations of student use of technology. When students are expected to demonstrate certain behaviors with ICTs those behaviors should be both supported and modeled by faculty and instructors. Secondly, when using ICTs for academic purposes, faculty can help students feel more responsible for their learning by providing them with opportunities to make decisions about how ICTs are used or to incorporate their own problem-solving or learning techniques with ICTs when completing coursework. Finally, faculty, instructors, and other staff should be aware that when first-year students are using ICTs socially, they are trying to create and maintain in-person relationships. Faculty, instructors, and other staff can guide first-year students to events and resources that will help them meet people and locate a social group in which they feel like they fit in.
Keywords: New literacies; Technology; First-year college students; Phenomenology; Higher Education (0745)